2007
DOI: 10.1303/aez.2007.329
|View full text |Cite
|
Sign up to set email alerts
|

Host-related morphological variation within Myzus persicae group (Homoptera: Aphididae) from Japan

Abstract: There have been independent long-term studies of tobacco-adapted populations of Myzus persicae in Japan and Greece, but until now no direct comparisons have been made between them. In Japan, as in Greece, tobacco aphids can reproduce sexually to some extent so that there is the potential for hybridisation with M. persicae from other plants on their common primary host, the peach. To determine whether Japanese tobacco aphids agree morphologically with those in Greece, and hence fit the concept of M. persicae ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…It has been long suspected that populations colonizing tobacco Nicotiana tabacum L. are different from those on other crops (De Jong, 1929; Brain, 1942). This was confirmed by multivariate morphometric studies (Blackman, 1987), which have also subsequently shown that the tobacco‐feeding form retains its host‐related properties through time, even in regions (Greece and Japan) where there is a bisexual generation on the shared primary host, the peach Prunus persica L. (Margaritopoulos et al ., 2000, 2003, 2007). Analysis of clonal lineages reared under controlled conditions on the same host plant proved that these differences have a genetic basis.…”
mentioning
confidence: 70%
“…It has been long suspected that populations colonizing tobacco Nicotiana tabacum L. are different from those on other crops (De Jong, 1929; Brain, 1942). This was confirmed by multivariate morphometric studies (Blackman, 1987), which have also subsequently shown that the tobacco‐feeding form retains its host‐related properties through time, even in regions (Greece and Japan) where there is a bisexual generation on the shared primary host, the peach Prunus persica L. (Margaritopoulos et al ., 2000, 2003, 2007). Analysis of clonal lineages reared under controlled conditions on the same host plant proved that these differences have a genetic basis.…”
mentioning
confidence: 70%
“…It is clear that the long-term or incipient speciation pattern of Aphis , especially in the gossypii group, by the transition that they have drastically shifted their hosts to many unrelated plants is quite different from most other species in Acyrthosiphon , Hyalopterus , Macrosiphoniella , Megoura , and Uroleucon within Aphidinae, which have diverged to the plant species closely associated within a genus or within a family [17], [18], [42], [43]. However, similar association to unrelated hosts occurring in Myzus persicae [24], [44], [45] must be associated with that in Aphis gossypii [38], [39], [46], which seems to similarly affect the noticeable changes of these morphological characters in morphometric analysis between specialized host-adapted populations [20], [47]. These two species have a lot of similarity in regard to polyphagy, and with displaying variations in life cycle, i.e., host alternation, monoecious holocycly, or anholocycly [2], so they may have similar speciation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite and multivariate morphometric analyses of persicae s.l . populations on a global scale indicate that the host shift to tobacco occurred only once, probably in eastern Asia (Blackman, ; Margaritopoulos et al ., 2007b; 2009). In addition, the genetic changes that enable nicotianae to detoxify nicotine have now been identified (Bass et al ., ).…”
Section: Introductionmentioning
confidence: 99%